P3_11 Concrete Shoes - Pilkington, Nathan; Perry, Michael; Bettles, John; Clarke, Iain (Physics Special Topics, 2011)
Â  This paper aimed to explore the minimum additional weight required to successfully submerge a 70kg human body in the buoyant waters of the Dead Sea. The analysis showed that a human body could be sunk with an additional weight of 11kg or greater.